2021
DOI: 10.3390/electronics10232953
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement Learning Aided UAV Base Station Location Optimization for Rate Maximization

Abstract: The application of unmanned aerial vehicles (UAV) as base station (BS) is gaining popularity. In this paper, we consider maximization of the overall data rate by intelligent deployment of UAV BS in the downlink of a cellular system. We investigate a reinforcement learning (RL)-aided approach to optimize the position of flying BSs mounted on board UAVs to support a macro BS (MBS). We propose an algorithm to avoid collision between multiple UAVs undergoing exploratory movements and to restrict UAV BSs movement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…No aprendizado por reforc ¸o (Reinforcement Learning -RL), os modelos são treinados para elaborar uma sequência de decisões. Neste paradigma, não existem dados de treinamento, pois os algoritmos se baseiam em um modelo de recompensas e punic ¸ões à medida que o agente interage com o ambiente [P G and Magarini 2021] .…”
Section: E Fl Como Habilitadores De Vants Em Redes Móveisunclassified
See 1 more Smart Citation
“…No aprendizado por reforc ¸o (Reinforcement Learning -RL), os modelos são treinados para elaborar uma sequência de decisões. Neste paradigma, não existem dados de treinamento, pois os algoritmos se baseiam em um modelo de recompensas e punic ¸ões à medida que o agente interage com o ambiente [P G and Magarini 2021] .…”
Section: E Fl Como Habilitadores De Vants Em Redes Móveisunclassified
“…Portanto, espera-se que os VANTs fornec ¸am servic ¸os de comunicac ¸ão para novas aplicac ¸ões inteligentes orientadas por dados [Brik et al 2020]. Nesse contexto, as abordagens assistidas por Aprendizado de Máquina (Machine Learning -ML) tem sido utilizadas extensivamente para fins de otimizac ¸ão e automac ¸ão [P G and Magarini 2021].…”
Section: Introduc ¸ãOunclassified
“…The deployment of a UAV by optimizing its trajectory to maximize the mean opinion score using a deep Q-learning method was presented in [23]. Similarly, the data rate maximization of an ABS-assisted downlink cellular system using RL was presented in [24]. Here, the Q-learning technique was used to optimize the ABS location, where simulation results revealed that RL performed better than a k-means algorithm to find the optimal ABS positions.…”
Section: Related Workmentioning
confidence: 99%
“…With learning-based methods are widely used [28]. In [29][30][31], methods such as YOLOv4-CSP, Q-learning and Deep Reinforcement Learning are used to improve the speed and accuracy of the algorithms. However, the algorithm cannot resolve whether the flight path follows the original global path planning method or performs local path planning first and then replans.…”
Section: Related Workmentioning
confidence: 99%